Analisis Kesulitan Siswa dalam Pembelajaran Bahasa Inggris di Sekolah Dasar - Mai Sri Lena; Sartono Sartono; Tiara Emilia; Sania Khairanis (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
This study aims to find out the difficulties experienced by students in learning English in elementary schools. Analysis of student difficulties was taken from the perspective of observing the teacher when students were learning English in elementary schools. Data collection techniques were carried out through questionnaires via the G-Form, which were distributed via social media with a target of 150 teacher respondents. From the questionnaire carried out by elementary school teachers, it can be concluded that the difficulties experienced by students in learning English at elementary school are inferred. achievement is the unachievedness of students who are not in accordance with the desired target. The difficulty factor in learning English is influenced by internal and external factors. From the results of this study a solution can be found that can be carried out by education in the future. Because English in this globalization era has an important role in various aspects.